2020
DOI: 10.3389/fmicb.2020.01275
|View full text |Cite
|
Sign up to set email alerts
|

New Methods, New Concepts: What Can Be Applied to Freshwater Periphyton?

Abstract: Microbial interactions play an essential role in aquatic ecosystems and are of the great interest for both marine and freshwater ecologists. Recent development of new technologies and methods allowed to reveal many functional mechanisms and create new concepts. Yet, many fundamental aspects of microbial interactions have been almost exclusively studied for marine pelagic and benthic ecosystems. These studies resulted in a formulation of the Black Queen Hypothesis, a development of the phycosphere concept for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 127 publications
(201 reference statements)
0
9
0
Order By: Relevance
“…This aspect was poorly described so far, as most studies looked either at the overall effluent toxicity (Liao et al, 2019;Nega et al, 2019;Peng et al, 2018;Romero et al, 2019), or at other wastewater constituents, such as nutrients (Lebkuecher et al, 2018) and micropollutants (Carles et al, 2021;Chonova et al, 2019;Tamminen et al, 2022;Tardy et al, 2021;Tlili et al, 2020). Our study also points towards the importance of species interactions within periphyton communities, as well as between prokaryotes and eukaryotes, which occur among co-existing species in periphyton (Gubelit and Grossart, 2020). For instance, studies on diatom-bacterial interactions revealed a high species-specific interdependence of the algal host and bacteria, as each diatom species developed a bacterial community that differed in its composition (Grossart et al, 2005;Koedooder et al, 2019;Stock et al, 2019).…”
Section: Identification Of Periphyton Taxa Impacted By Wastewater Mic...mentioning
confidence: 85%
“…This aspect was poorly described so far, as most studies looked either at the overall effluent toxicity (Liao et al, 2019;Nega et al, 2019;Peng et al, 2018;Romero et al, 2019), or at other wastewater constituents, such as nutrients (Lebkuecher et al, 2018) and micropollutants (Carles et al, 2021;Chonova et al, 2019;Tamminen et al, 2022;Tardy et al, 2021;Tlili et al, 2020). Our study also points towards the importance of species interactions within periphyton communities, as well as between prokaryotes and eukaryotes, which occur among co-existing species in periphyton (Gubelit and Grossart, 2020). For instance, studies on diatom-bacterial interactions revealed a high species-specific interdependence of the algal host and bacteria, as each diatom species developed a bacterial community that differed in its composition (Grossart et al, 2005;Koedooder et al, 2019;Stock et al, 2019).…”
Section: Identification Of Periphyton Taxa Impacted By Wastewater Mic...mentioning
confidence: 85%
“…Unlike in cooling towers, biofilms in lakes are hotspots for biodiversity, with a wide variety of microorganisms and their grazers in numerous ecological niches [ 69 , 70 ]. However, no L. pneumophila could be detected in the investigated swimming lakes, although the water temperature (mean: 25.1 °C, Table S1 ) during the sampling period was suitable for its growth [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Black empty ellipses highlight how exposure times are discriminated although further investigations are still needed to provide quantitative evidence of this causal relationship. In addition, this fatty acid, as others, has been described as antibacterial or as growth inhibitor of some algae species (i.e., involved in allelopathic interactions) (Allen et al 2015, Gubelit andGrossart 2020). Hence, their downregulation might trigger shifts in community composition and so its functioning and associated ecosystem functions supported by these microbial communities.…”
Section: The Biofilm Metabolomics Fingerprint Changes Along Exposure Time To Diuronmentioning
confidence: 91%